Optimal Planning on Reactive Power Compensation of Distribution Network Based on Back/Forward Sweep Method and Tabu Search Algorithm - Wang, Xiao Wen; Zhao, Yan Hui (Applied Mechanics and Materials, 2014)
This paper proposes the optimization method on reactive power compensation of distribution network. The objective is that total loss difference between before being compensated and after should get maximum. The method adopts back/forward sweep method for calculating power flow to obtain total active network loss. Then global neighborhood searching strategy and aspiration criterion for fixed parallel capacitor are established by tabu search algorithm. The optimal installation location and compensation capacity of fixed parallel capacitor are determined. Optimizing simulation on a 34 nodes distribution system is realized, and optimal planning scheme is obtained. Results show that the proposed method is feasible and effective in optimal planning on reactive power compensation of distribution network.